FAKTOR YANG MEMPENGARUHI AKSI KORPORASI, RASIO KEUANGAN DAN FUNDAMENTAL EKONOMI MAKRO TERHADAP HARGA SAHAM - Diana , Bella Nur; Suhartono, Entot (Jurnal Riset Akuntansi (JUARA), 2021)
Purpose of this research to find out the ROA, DER, EPS, PER, DPS , interest rates, and exchange rates to shares. This study used manufacturing sample companies that are widely available on the Indonesia Stock Exchange (IDX) for the period 2017-2019. Sample 38 companies with purposive sampling method. This study uses SPSS. The results of the study were the ROA, DER, DPS, interest rates, and exchange rates, affect insignificant the share price. While EPS and PER are significant against the share price.